Fixed Assets Information System at PT.Pln (Persero) North Sumatra - Yolanda Sari (Trigin Publisher, 2023)
Depreciation is the allocation of the acquisition price of fixed assets into expenses into the accounting period that enjoys the benefits of these fixed assets, there are three factors that need to be considered in determining the depreciation expense for each period, namely the acquisition price is the entire amount of money spent to acquire an asset used by the company, residual value is the estimated selling price of the fixed assets at the end of the useful life of the fixed assets, the amount of the estimated residual value will also be greatly influenced by its economic age, inflation, currency exchange rates, line of business and so on. The estimated useful life is the estimated useful life of the fixed assets. The useful life is the estimated economic life of the fixed assets, not the technical life. The estimated useful life can be expressed in units of a year's period. Therefore the application is made using the Visual Basic programming language. Net 2010 and SQL Server 2008 as the database. With the existing tools in the calculation of depreciation of fixed assets, it can assist companies in making depreciation reports that exist in these companies